2000
DOI: 10.1039/b005879n
|View full text |Cite
|
Sign up to set email alerts
|

Improved measurement of iodine in food samples using inductively coupled plasma isotope dilution mass spectrometry

Abstract: A new ICP-MS method for the determination of iodine in food samples is presented. The method makes use of a new miniature cyclonic spray chamber and a concentric glass nebulizer that is designed for low sample uptakes and is operated in a self-aspirating mode. As a consequence the wash-out was accelerated over conventional systems. This configuration allows the direct determination of iodine in mineralized solutions following digestion with nitric acid only. No strong oxidizing reagents such as perchloric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 29 publications
(46 reference statements)
0
60
0
Order By: Relevance
“…For ICP-MS, the signals are just slightly enhanced with respect to a double pass spray chamber and the wash out times found with the Cinnabar are significantly shortened [138]. Due to its simplicity and the small dispersion arising with this spray chamber, it has been successfully applied as a CE-ICP-MS interface [139].…”
Section: Low Inner Volume Cyclonic Spray Chambermentioning
confidence: 99%
“…For ICP-MS, the signals are just slightly enhanced with respect to a double pass spray chamber and the wash out times found with the Cinnabar are significantly shortened [138]. Due to its simplicity and the small dispersion arising with this spray chamber, it has been successfully applied as a CE-ICP-MS interface [139].…”
Section: Low Inner Volume Cyclonic Spray Chambermentioning
confidence: 99%
“…ICP-MS allows direct determination of iodine in urine. Application of isotope dilution analysis using I 129 as a spike as well as the instrumental design permit automatic, accurate and reproducible measurements (Haldimann et al, 1998(Haldimann et al, , 2000. In order to conform with the international scientific literature on the matter, results were expressed as mg I=l urine and as mg I=g creatinine.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…One study found differences in BMIC between fore-and hind-milk samples (17) while another did not (18). Broad ranges of BMIC have been reported in iodine-sufficient countries (9)(10)(11)19), but comparing BMIC across studies is difficult because of differences in study design, analytical methods, and the lack of external quality control (9,17,(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%